BIOPHILIC DESIGN AS A WAY TO IMPROVE WORKING CONDITIONS AND THE MICROCLIMATE OF OFFICE PREMISES - Andriienko, Olha; Panyuta, Olha (Theory and practice of design, 2023)
The article is devoted to the study of biophilic design as a way to improve the working conditions and microclimate of office premises. The purpose of this study is to show and explain that the decoration of office space with plants is extremely important for creating a comfortable working environment. Also, to investigate the consequences of urbanization, the construction of office blocks and industrial centers and to find ways to improve the environmental situation through landscaping. Methodology. The theoretical general scientific method of research was used, namely, the analysis of available data and published materials. Results. The literature review revealed how rapid urbanization affects the environment, which affects the emotional and physical comfort of a person in the workplace. The importance of greening office space is emphasized. It is necessary to solve the problem of high levels of stress, workload and emotional stress of employees. Recommendations for the development of project compositions of biophilic design are formulated. This includes the inclusion of natural elements in the interior such as stones, water, natural materials, specific sounds, plants, animals, colors, etc. The importance of continuing research in the field of biophilic design to improve the ways and methods of its reproduction is emphasized. Scientific novelty. Several ways of organizing vertical gardening are proposed. The dependence of the physical and emotional state of a person on nature is substantiated. Practical relevance. The results of the study can be used as a theoretical basis for the development of biophilic office design to improve working conditions.